Phase Equilibria of Fluoride‐Free Boracic Mould Flux for Steel Continuous Casting. Issue 6 (18th February 2015) - Cui, Yaru; Wang, Lin; Yang, Jian; Zhang, Jianqiang; Sasaki, Yasushi; Ostrovski, Oleg; Yu, Aibing
<x xml:space="preserve">Abstract</x> Development of fluoride‐free mould flux is important for steel continuous casting. Properties of the mould flux depend on the flux crystallinity. This paper analyzes phase composition of fluxes containing B2O3, TiO2, Na2O, and MgO which can be feasible candidates to replace the fluorides. The phase equilibria of these fluoride‐free boracic mould fluxes were calculated using the thermochemical software FACTSage. In the process of crystallization of the CaOSiO2Al2O3B2O3Na2O flux with high CaO/SiO2, combeite (Na2, Ca)Na2CaSi3O9, Ca11B2Si4O22, and nepheline NaAlSiO4 were formed, which can substitute cuspidine in the fluoride‐containing fluxes. At high CaO/SiO2, adding MgO into CaOSiO2Al2O3B2O3Na2OTiO2 mould flux remarkably increased crystallization temperature by forming merwinite (Ca3MgSi2O8), decreasing the relative crystal phase contents of (Na2, Ca)Na2CaSi3O9 and Ca11B2Si4O22. The calculated data were in reasonable agreement with results of XRD and SEM/EDS analyses of selected boracic fluxes.